The Influencing of Causal Factors Repurchasing Intention Cosmetics on Facebook Fanpage of Consumers in Bangkok and Its Vicinity - Pankham, Sumaman; Kongkuthong, Rapeeporn (Arts of Management Journal, 2021)
This article aimed to 1) develop and validate the consistency a causal factor repurchasing intention cosmetics on Facebook Fanpage of consumers in Bangkok and its vicinity; 2) study about the influencing of causal factors repurchasing intention cosmetics on Facebook Fanpage of consumers in Bangkok and its vicinity. The sample group consisted of 215 people who have repurchasing cosmetics on Facebook Fanpage. The tools used in the research were online questionnaires. The statistics used in data analysis were frequency, percentage, and structural equation model. The results of this research were causal relationships to develop consisting of 4 components were 1) Satisfaction 2) Trust 3) Loyalty and 4) Repurchase Intention and the model was consistent with the empirical data to a great extent. The statistic showed the Chi-square statistics goodness fit test ( 2) = 157.78, degrees of freedom (df) = 151, CMIN / DF = 1.04, GFI = 0.93, AGFI = 0.90, SRMR = 0.03, RMSEA = 0.01. The final was predictive coefficient of 0.97, indicating that the variables in the model can explain the variance of the repurchase intention of cosmetics on Facebook Fanpage by 97 percent. It was found that the consumer attitudes were the most influence on repurchase intention of cosmetics on Facebook Fanpage of the consumers in Bangkok and its vicinity. The results of this research were useful for entrepreneurs, owner of cosmetics on Facebook Fanpage businesses were utilized to the marketing plan and create marketing strategies that were suitable for consumers. Resulting in repurchasing intention to the online course in the future.